2016
DOI: 10.1017/s0003975616000047
|View full text |Cite
|
Sign up to set email alerts
|

Governing Science

Abstract: This review explores contributions by science policy studies and the sociology of science to our understanding of the impact of governance on research content. Contributions are subsumed under two perspectives, namely an "impact of"-perspective that searches for effects of specific governance arrangements and an "impact on"-perspective that asks what factors contribute to the construction of research content and includes governance among them. Our review shows that little is known so far about the impact of go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(44 citation statements)
references
References 186 publications
(209 reference statements)
1
35
0
3
Order By: Relevance
“…Thus, current funding mechanisms limit transitions towards new research topics and encourages researchers to engage in scientific "window dressing" [90]. Gläser and Laudel [42] regards "window dressing" as a way to "bootleg money for the start of new research under the cover of existing grants" (p. 125). Our results showed that this practice occurred in the studied projects as some coordinators reported on the "hidden research agendas" of researchers who followed their individual research interests and contributed little to the joint projects.…”
Section: Academic Structures and Cultures Do Not Integrate Well With Tdrmentioning
confidence: 99%
“…Thus, current funding mechanisms limit transitions towards new research topics and encourages researchers to engage in scientific "window dressing" [90]. Gläser and Laudel [42] regards "window dressing" as a way to "bootleg money for the start of new research under the cover of existing grants" (p. 125). Our results showed that this practice occurred in the studied projects as some coordinators reported on the "hidden research agendas" of researchers who followed their individual research interests and contributed little to the joint projects.…”
Section: Academic Structures and Cultures Do Not Integrate Well With Tdrmentioning
confidence: 99%
“…There is relatively little empirical work on the relation between funding arrangements and organizational and epistemic properties of research (but see Heinze 2008 ; Heinze et al 2009 ). To study this relation a bridge between science policy studies, strong in the analysis of funding mechanisms, and science studies, strong in the analysis of organizational and epistemic properties of research, is necessary (Gläser and Laudel 2016 ). In recent years, in relation to the rise of the ERC funding schemes, a group of studies that aim to do exactly this has appeared.…”
Section: Introductionmentioning
confidence: 99%
“…Research communities are embedded in specific social contexts, for example in geographical, linguistic, and disciplinary contexts, which influence what a research community considers as subjects of interest in their research field and as good scholarship standards (Gläser and Laudel, 2016;Hess, 2016, p. 162).…”
Section: Introductionmentioning
confidence: 99%